UAV AERIAL SURVEY IN MONITORING OF COASTAL GEOSYSTEMS IN THE SOUTHERN IRKUTSK AMPHITHEATRE - O. A. Mazaeva; A. A. Yuriev; V. A. Babicheva (Геодинамика и тектонофизика, 2023)
Estimating the dynamics of exogenous geological processes and understanding their controlling factors is an urgent task faced by many regions of the world. One of the methods of its solution is monitoring. The paper presents the UAV monitoring results for short-term dynamics of complex exogenous processes at five key sites in the coastal zone south of the Bratsk reservoir. The study area is a part of the platform structure in the south of the Irkutsk amphitheater, which is considered to be relatively stable in terms of geodynamics. There has been developed a methodical scheme for obtaining data series on the dynamics of complex exogenous geological processes in the coastal geosystem. A flight altitude of 50–60 m is optimal to obtain orthophotos with a resolution of 1.1–2.2 cm/px, sufficient to estimate the areal dynamics of the processes, and a DEM with a resolution of 2.6–5.4 cm/px to estimate the volumetric dynamics.The eroded coastal area at the Rassvet site was measured to be 6900 m2, which corresponds to an average erosion width of 3.45 m per linear meter of coastal length with maximum values of up to 6.51 m. A high rate of coastal erosion in the period 2021–2022 is related to the maximum water level in the Bratsk reservoir, close to the normal headwater level. The assessment of the volumetric dynamics of the coastal gullies yielded negative values, as most of the gully mouths were eroded. The secondary valley-bottom gullies (Mamontov and Barany sites) and coastal gullies (Khadakhan site) are characterized by positive dynamics both in area and volume growth (12–20 m2 and 1.3–35.0 m3, respectively). At the Khadakhan site, the volumetric growth of new and previously observed suffusion sinkholes was 0.45 m3.The obtained areal and volumetric rates of the exogenous processes can serve as a basis for their modern assessment and prediction of their development in order to prevent and reduce socio-economic risks.